The quick fix guide to academic writing : - Shon, Phillip C. (SAGE Publications Inc, 2018)
roviding you with a quick set of writing rules to follow, this tried and tested guide uses a unique and easy to follow grid-based system. Packed with advice on understanding (big and little) common errors made in academic writing, it helps you identify patterns in your own writing and demonstrates how to reshape or re-evaluate them - and raise your writing game in any academic context. Synthesizing and critiquing literature – and using your coding sheet to develop critical arguments. Shaping abstracts, introductions, discussions, and conclusions – to improve the logic and structure of your writing. Applying lessons-learned to future projects, whatever format of academic writing.